Islamophobia_Discrimination Against Muslims in America in Attempt to Maintain Global Hegemony - Sayyidah ‘Nisa (Proceedings University of Muhammadiyah Yogyakarta Undergraduate Conference, 2022)
2 and has spread since 9/11 when a terrorist attack brought down the Twin Towers of the World Trade Center (WTC) in New York. In its history, America is the inheritor of the "Western Domination" of Europe during the imperialism era. Then with an increasingly advanced era, globalization is increasingly demanding to carry out all foreign policies of a country that does not contain elements of violence and upholds peace. So America uses soft power in issuing all its policies, one of which is related to the issue of Islamophobia. The number of issues of anti-Islam discrimination in the west has attracted a lot of international attention, so this is the reason why the writer investigates this matter. The purpose of this study is to find out the American Strategy on Islamophobia to uphold world hegemony. By using descriptive qualitative research analysis techniques and literature studies such as sources from books, journals, documents, and reports. The author finds that America uses all the power it has to influence other countries. This finding is corroborated by the concept of framing in the media to spread Islamophobia. By relying on its strength, America gets financial assistance from various lines as a supporter of US policy. In addition, the author also analyzes the constructivist theory approach where all phenomena that occur are based on construction results with various national interests and actors behind them. In the end, it aims to find out the indications and objectives of the current and future United States foreign policy in its international politics as well as efforts to minimize anti-Islamic sentiment in the west. what happened in 1992?